Vocational College Students’ Perceptions on The Use of Computer English MOOC in Hybrid Learning - Wei Wei; Noraini Said; Jiang Tao (Human Resource Management Academic Research Society, 2024)
Introduction: The advancement of educational technology and the widespread adoption of network technology in education have drawn significant attention from educational circles. Massive Open Online Courses (MOOCs) have emerged as a popular platform for learners to access and utilize educational resources. Objective: This paper aims to investigate various aspects of hybrid learning in the Computer English MOOC platform, including students' learning objectives, methods, concentration, collaborative skills, teaching observation, and learning efficiency. Methodology: The research utilizes a quantitative approach to analyze data obtained from 169 vocational college students majoring in computer-related subjects. Findings: The study reveals six key findings. Despite the challenges imposed by the Covid-19 pandemic, students maintain clear objectives for learning Computer English. Implications: This investigation serves as both a theoretical and empirical exploration of hybrid learning in the context of MOOCs. This research underscores the positive impact of educational technology and hybrid learning on students' learning experiences. It emphasizes the value of MOOCs and encourages teachers to embrace innovative teaching approaches to promote effective and efficient learning outcomes. By integrating technology into teaching procedures, educators can further enhance students' learning potential motivation and equip them with the necessary skills for success. Significance of Study: This study lies in its potential to bridge the existing knowledge gap regarding the specific factors that impact English language acquisition within the vocational college setting. This research seeks to provide valuable insights and recommendations to inform pedagogical practices, curriculum development, and institutional policies in higher vocational colleges in China.